1981
DOI: 10.1159/000232735
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid Clustering and Mast Cell Degranulation

Abstract: It was shown using spin-labelled probes that challenge of sensitized rat peritoneal mast cells results in clustering of sphingolipids located in the outer leaflet of the plasma membrane bilayer. This clustering is partially inhibited by antiallergic drugs of the chromone type. It is hypothesized that the sphingolipid clustering may be involved in the Ca++ gate mechanism which is associated with anaphylactically-induced mast cell degranulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Application of Model II not only allows deconvolution of intermediate-range spectra into 'dilute' and 'concentrated' components, but also permits accurate simulation of spectral features observed experimentally at high loading (Figs. [6][7][8][9][10][11]. Consistent with the model's prediction that 'dilute' sites will be lost at high P/L, the ratio of 'dilute' to 'concentrated' decreases dramatically (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Application of Model II not only allows deconvolution of intermediate-range spectra into 'dilute' and 'concentrated' components, but also permits accurate simulation of spectral features observed experimentally at high loading (Figs. [6][7][8][9][10][11]. Consistent with the model's prediction that 'dilute' sites will be lost at high P/L, the ratio of 'dilute' to 'concentrated' decreases dramatically (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…The interplay between sphingolipid signaling and mast cell biology has long been appreciated, with the first report that sulfatides could be isolated from neoplastic mast cells in 1960 (GREEN & ROBINSON, 1960). Some 20 years later, Curtain et al demonstrated that sensitizing rat peritoneal mast cells resulted in glycosphingolipid clustering in the plasma membrane which was critical for degranulation (Curtain et al, 1981). Katz et al extended these studies to show that sphingolipid reorganization was not only a marker of mast cell activation but was useful in discerning subtypes of murine mast cells (Katz and Austen, 1986; Katz et al, 1985).…”
Section: Introductionmentioning
confidence: 99%